The Complex Relationship Between Diabetes and Cardiac Arrhythmias: Pathophysiology and Mechanisms - Spartalis, Michael; Pantelidis, Panteleimon; Kontogiannis, Christos; Paschou, Stavroula A.; Spartalis, Eleftherios; Iliopoulos, Dimitrios C.; Siasos, Gerasimos (Current Pharmaceutical Design, 2022)
Coronary artery disease, autonomic neuropathy, and diabetic cardiomyopathy are the most common cardiovascular complications of diabetes. However, emerging evidence demonstrates that diabetes also affects the heart’s electrical conduction system, culminating in lethal arrhythmias and sudden cardiac death. Diabetes and rhythm disturbances have a complex relationship, and arrhythmias cannot only be attributed to ischemia and autonomic neuropathy. Hypoglycemia, hyperglycemia, and glucose fluctuations can potentially induce arrhythmias by activating various pathways. Structural remodeling can accelerate and exacerbate disease development. Mitochondrial dysfunction can also alter the structure and metabolism of cardiomyocytes and contribute to disease progression through oxidative stress and inflammation.
Keywords: cardiovascular